Critical Analysis of Adoption Behaviour of Rice (Oryza sativa L.) Production Technologies by the Farmers- A Case Study through Krishi Vigyan Kendras (KVKs) in North Eastern Region - Singha, A. K.; Tripathi, A. K.; Jat, P. C.; Bordoloi, R.; Singha, J. K.; Devi, Merina (Indian Journal of Hill Farming, 2018)
This study to analyse the adoption behaviour of farmers of rice technology was conducted in 13 purposively selected KVK districts in the region. A sample size of 130 respondents from each adopted and non-adopted villages was taken through proportionate random sampling. Data collection from the selected respondents was made with the help of pre-tested structured schedule through personal interview method. The study reveals that over half of the respondents in KVKs adopted villages had medium level of adoption of improved rice cultivation practices, while majority with over half of the total respondents in non-adopted villages were found poor adoption level of the same rice practices. Respondents of non-beneficiary farmers was found little adoption of recommendations of practices like seed rate, seed treatment using chemicals and bio-pesticides, application of manures and fertilizers and use of chemicals and bio-pesticides as plant protection measures, however, beneficiary farmers had reported medium extent of adoption of these practices. The study further shows that out of 13 independent variables under study, education and extension contact were found having positively significant relationship with the extent of adoption of improved rice cultivation practices. While three variables namely, type of primary farming activities, training received and extension contact had emerged as the most dominant factors influencing farmers to extent of adoption of improved rice cultivation practices.